2016
DOI: 10.17795/nmsjournal27763
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of a Screening Instrument for Domestic Violence in a Sample of Iranian Women

Abstract: BackgroundDomestic violence against women is regarded as an important health problem among women and a serious concern in issues related to human rights. To date, a few screening tools for domestic violence exist for Iranian married women, but they assess only some of the domestic violence components.ObjectivesThe present study aimed to design and determine the validity and reliability of a screening instrument for domestic violence in a sample of Iranian women.Materials and MethodsThe present study was a cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…This is consistent with the results of the current study, except for the negotiation violence. In a study, psychological, physical, sexual and total violence was reported 18.12%, 14.1%, 12.08%, and 44.47% respectively 12 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is consistent with the results of the current study, except for the negotiation violence. In a study, psychological, physical, sexual and total violence was reported 18.12%, 14.1%, 12.08%, and 44.47% respectively 12 .…”
Section: Discussionmentioning
confidence: 96%
“…Some surveys showed that women living in developing countries experience more violence than women in developed countries 8,11 . However, generally, no country is exempt from physical and psychological harm due to violence 12 .…”
Section: Introductionmentioning
confidence: 99%
“…However, as it is important to evaluate test factors when interpreting results, an exploratory factor analysis was performed using principal factor analysis, and the loadings were estimated with promax rotation to determine the CTSD factor structure. An eigenvalue > 1 and a loading factor > 0.3 [ 14 ] were considered. The analyses were conducted with SPSS version 23 (IBM, Armonk, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, acceptance of physical violence against women seems to be widespread, as 63% of women participating in a survey study conducted in Iraq indicated that they approved of the use of beatings in partnerships ( Linos et al, 2012 ). Despite its comparatively high IPV levels, the Middle East is among the regions for which very few validated IPV instruments exist ( Boy and Kulczycki, 2008 ; Azadarmaki et al, 2016 ), one of the few exceptions is the Arab version of the Composite Abuse Scale ( Alhabib et al, 2013 ). Hence, additional IPV instruments are necessary, which consider the full variety of experiences of women living in the context.…”
Section: Introductionmentioning
confidence: 99%